Co-phasing a segmented mirror telescope using a deformable mirror and phase diversity - Miyamura, Norihide (SPIE, 2019)
For small satellite remote sensing missions, a large aperture telescope which has more than 400 mm of diameter is required to realize less than 1m GSD observations. However, it is difficult or expensive to realize the large aperture telescope using monolithic primary mirror with high surface accuracy. Generally, not only high accuracy of optical surface but also high accuracy of optical alignment is required for large aperture telescope. For a segmented mirror telescope, aligning optical elements in high accuracy is more difficult and more important. For conventional systems, optical alignment is adjusted before launch to achieve desired imaging performance. However, it is difficult to adjust the alignment for large sized optics in high accuracy. Furthermore, thermal environment in orbit and vibration in launch vehicle cause the misalignments of the optics. We are developing an adaptive optics system using a MEMS deformable mirror (DM) for Earth observing remote sensing sensor. Image based adaptive optics system compensate the misalignments and wavefront aberration of optical elements using DM by feedback of observed images. Because, it is difficult to use a reference point source unless the satellite controls its attitude toward a star for Earth observing systems. Furthermore, total amount of incident light can enter an image sensor. We propose the control algorithm of DM and mirror segments for a segmented mirror telescope by using of observed images. Numerical simulation results represent that misalignment and wavefront aberration of the segmented mirror telescope are corrected and image quality is improved.